ESP Needs Analysis for Computer and Network Engineering Students at a Vocational High School in Bandar Lampung - Muhammad Rizki Amarta; Nurul Puspita; Istiqomah Nur Rahmawati (Universitas Islam Negeri Palopo, 2026)
This study investigated the English for Specific Purposes (ESP) needs of Computer and Network Engineering (TKJ) students at a vocational high school in Bandar Lampung, Indonesia. Guided by Hutchinson and Waters’ needs analysis framework, it examined students’ necessities, wants, lacks, and the alignment between current English materials and vocational demands. A mixed-methods case study involved 36 eleventh-grade students, one English teacher, and one TKJ teacher. Data were collected through a questionnaire, semi-structured interviews, and document analysis, then analyzed using descriptive statistics, thematic analysis, and document interpretation. The findings showed that students needed English mainly for technical instructions, tutorial videos, technical vocabulary, documentation, and workplace communication. They preferred hands-on, collaborative, task-based, and technology-related learning activities. Their main gaps were low confidence in professional English use, difficulty explaining technical concepts, limited technical vocabulary, and dependence on translation tools. Document analysis indicated that current materials remained general and lacked sufficient TKJ-related vocabulary, authentic technical texts, and workplace tasks. The novelty lies in triangulating student needs, teacher perspectives, and school documents within one TKJ context, showing that the mismatch is a curriculum-material issue. The study recommends ESP-oriented material adaptation through collaboration between English and vocational subject teachers.